A cost estimation approach for IoT modular architectures implementation in legacy systems - Tedeschi, Stefano; Emmanouilidis, Christos; Erkoyuncu, John Ahmet; Rodrigues, Duarte Polonia; Roy, Rajkumar; Starr, Andrew (Elsevier, 2018)
Industry 4.0 has encouraged manufacturing organisations to update their systems and processes by implementing Internet of Things (IoT) technology in legacy systems to provide new services such as autonomous condition monitoring and remote maintenance. However, there is still no literature that guides in realizing the advantages and disadvantages of the fourth industry revolution in terms of complexity, data security, and cost. This paper lays the foundation for the creation of an innovative conceptual model to estimate the cost for implementation of new architectures for legacy systems. The proposed approach considers aspects that impact the cost of different IoT architectures such as: complexity, data gathering and sharing protocols, and cyber security. The authors suggest a further implementation of the cost model, in order to guide the organisations in the most cost-effective architecture for modernisation of their legacy systems.
Keywords: Smart Manufacturing; IoT; Cost Estimation; Modular Architectures; Legacy Systems